2019
DOI: 10.1038/s41588-019-0504-x
|View full text |Cite
|
Sign up to set email alerts
|

Target genes, variants, tissues and transcriptional pathways influencing human serum urate levels

Abstract: Elevated serum urate levels cause gout, and correlate with cardio-metabolic diseases via poorly understood mechanisms. We performed a trans-ethnic genome-wide association study of serum urate among 457,690 individuals, identifying 183 loci (147 novel) that improve prediction of gout in an independent cohort of 334,880 individuals. Serum urate showed significant genetic correlations with many cardio-metabolic traits, with genetic causality analyses supporting a substantial role for pleiotropy. Enrichment analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
317
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 310 publications
(344 citation statements)
references
References 132 publications
15
317
1
2
Order By: Relevance
“…Hyperuricemia is the outcome of a combination of an endogenous purine metabolism disorder and an exogenous environmental disruption [37]. Recently, a trans-ancestry genome-wide association study, which included more than 450,000 individuals targeted at serum urate demonstrated that 183 loci were associated with gout [15]. However, few studies have focused on exogenous factors, such as dietary factors, that induce hyperuricemia or gout.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hyperuricemia is the outcome of a combination of an endogenous purine metabolism disorder and an exogenous environmental disruption [37]. Recently, a trans-ancestry genome-wide association study, which included more than 450,000 individuals targeted at serum urate demonstrated that 183 loci were associated with gout [15]. However, few studies have focused on exogenous factors, such as dietary factors, that induce hyperuricemia or gout.…”
Section: Discussionmentioning
confidence: 99%
“…ABCG2 is also expressed in intestine, and many patients with hyperuricemia lost the expression of ABCG2 in intestines. The current researches based on genome-wide association study (GWAS) analysis almost focus on the comparison between patients and healthy people, and the results displayed the difference in these genes including ABCG2, SLC2A9, HNF1A, HNF4A, ALDH2, CNTN5, MIR302F and so on [15,16]. The mechanism of developing hyperuricemia and gout and the reasons for disruption or mutation in these genes remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Among the other top hits, five are close to transcription factors involved in kidney and liver development (HNF4G, HNF1A, HNF4A, HLF and MAF). These are not part of a globally enriched gene set, but recent functional work has shown that the associated missense variant in HNF4A results in differential regulation of the urate solute carrier ABCG2 [17], while the MAF association has been shown to regulate SLC5A8 [20]. Finally, two other loci show large signals: a missense variant in INHBC, a TGF-family hormone, and a variant in/near GCKR, a glucose-enzyme regulator.…”
Section: Genetics Of Serum Urate Levelsmentioning
confidence: 99%
“…The pathogenesis of gout is thought to require progression through three checkpoints: hyperuricaemia (HU), deposition of monosodium urate (MSU) crystals into articular and peri-articular structures, and an inflammatory response to these crystals [1]. Genome-wide association studies (GWAS) have emphasised the contribution to urate control of genetic variation in renal and gut urate transporters, including SLC2A9 and ABCG2 [2,3]. When combined, variants in these two genes explain 3-4% of variance in urate levels and have strong effects on the risk of gout [4,5].…”
Section: Introductionmentioning
confidence: 99%